Landscape scale habitat suitability modelling of bats in the Western Ghats of India: Bats like something in their tea. (November 2015) - Wordley, Claire F.R.; Sankaran, Mahesh; Mudappa, Divya; Altringham, John D.
Abstract: To conserve biodiversity it is imperative that we understand how different species respond to land use change, and determine the scales at which habitat changes affect species' persistence. We used habitat suitability models (HSMs) at spatial scales from 100–4000 m to address these concerns for bats in the Western Ghats of India, a biodiversity hotspot of global importance where the habitat requirements of bats are poorly understood. We used acoustic and capture data to build fine scale HSMs for ten species ( Hesperoptenus tickelli, Miniopterus fuliginosus, Miniopterus pusillus, Myotis horsfieldii, Pipistrellus ceylonicus, Megaderma spasma, Hipposideros pomona, Rhinolophus beddomei, Rhinolophus indorouxii and Rhinolophus lepidus ) in a tea-dominated landscape. Small (100–500 m) scale habitat variables (e.g. percentage tea plantation cover) and distances to habitat features (e.g. distance to water) were the strongest predictors of bat occurrence, likely due to their high mobility, which enables them to exploit even small or isolated foraging areas. Most species showed a positive response to coffee plantations grown under native shade and to forest fragments, but a negative response to more heavily modified tea plantations. Two species were never recorded in tea plantations. This is the first study of bats in tea plantations globally, and the first ecological Old World bat study to combine acoustic and capture data. Our results suggest that although bats respond negatively to tea plantations, tea-dominated landscapes that also contain forest fragments and shade coffee can nevertheless support many bat species. Highlights: First study of bats in tea plantations, first fine scale tropical bat HSM. Many bats live in tea dominated landscapes if there is adequate native tree cover. Shade coffee with native trees can be suitable even for some forest specialist bats. Replanting even small forest patches will help bats, including forest specialists. Riparian areas are important for all species not just riparian specialists.